SEJARAH PERTUMBUHAN DAN PERKEMBANGAN LEMBAGA KEAGAMAAN NON FORMAL DI KABUPATEN BONE SULAWESI SELATAN - L., Idrus (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study discusses the history of the growth and development of Islamic boarding schools in Bone Regency, South Sulawesi, from the time of the Islamic kingdom/sultanate until the post-reformation era. This research is descriptive analytic, namely the data obtained in the form of opinions, information and behavior in a qualitative form which has a broader meaning by examining and researching focused on written sources only and interviewing religious figures related to the research theme. The results showed that Al-Mujahidin mosque which was founded in 1639 AD by Qadi (Judge) Fakih Amrullah, was the epicenter of the embryonic growth and development of early Islamic boarding school in Bone which later gave birth to several Islamic boarding schools with salafiyah/traditional and khalafiyah/modern patterns both formally and non-formally.